KAJIAN HUKUM TERHADAP PERLINDUNGAN BAGI PELAKU PEREKAMAN DAN PENYERAHAN REKAMAN YANG BERMUATAN ASUSILA DITINJAU DARI UNDANG-UNDANG ITE - Andreas Jaya Hartanu (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2023)
ABSTRACT Basically, all legal actions related to acts of sexual harassment, especially verbally through electronic media, have been strictly regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. However, in practice there are still acts committed by a principal who has verbally sexually harassed through a telephone conversation to an honorary teacher at the place where he works. So the honorary teacher took the initiative to record the perverted conversation and handed it over to his friend to report to the authorities, but it was actually disseminated by his friend. So that this has violated the legal provisions contained in Article 27 paragraph (1) of the ITE Law. Therefore, there is a need for legal protection for perpetrators who record and submit recordings charged with violating decency as a form of protection for themselves as victims in order to obtain justice for the perverted behavior that befell them.